The role of participants in education research : ethics, epistemologies, and methods - Midgley, Warren.; Danaher, Patrick Alan, 1959-; Baguley, Margaret, 1966- (Routledge research in education ;, 2013)
"This book explores different perspectives on the role, influence and importance of participants in education research. Drawing on a variety of philosophical, theoretical and methodological approaches, the book examines how researchers relate to and with their participants before, during, and after the collection and/or production of data; reimagining the rights of participants, the role/s of participants, the concept/s of "participant" itself"--